Effects of trial duration on estimates of critical power and time-trial prediction during field cycling - Gumpenbeger, M.; Heider, S.; Nimmerichter, A. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The hyperbolic response between power and duration is characterised by an asymptote (critical power; CP), which theoretically represents the maximum rate of work that can be maintained for a very long time without fatigue and a finite amount of work that may be performed above CP (W`). Traditionally CP and W` are estimated from 3-5 constant power ergometer trials leading to exhaustion within 1-12 min. It has been shown that the range of duration can affect estimates of CP. Therefore, the aim of this study was to determine the effect of trial-duration on estimates of CP in field conditions. In addition, the accuracy of CP to predict 20-min time-trial power (TT20) was assessed. We hypothesised that different trial-duration result in similar CP estimates and accurately predict TT20. Methods: Ten male endurance trained cyclists (mean ± SD, age: 31.4 ± 5.8 years, body mass: 76.8 ± 6.0 kg, VO2max: 60.0 ± 4.1 ml/kg/min) completed three maximal-effort sessions on flat roads, on a racing bike equipped with a mobile power-meter (SRM). To estimate CP, trials of 1, 4, and 10 min (CP1), and 2, 7, and 12 min (CP2) interspersed by 30 min, were performed during session one and two, respectively. During session three, the TT20 was conducted. CP1 and CP2 were modelled using the linear work/time relationship. In addition, a third set consisting all trials from 1-12 min (CP3) was used to estimate CP. Repeated measure ANOVA was used to compare CP and TT20 across the trials. The standard error of estimate (SEE) from linear regression analysis was used to assess prediction accuracy. Results: There were no significant differences between CP1 (305 ± 38 W), CP2 (298 ± 35 W), CP3 (301 ± 35 W) and TT20 (317 ± 31 W) (F3,7 = 3.1; p = 0.1). Strong correlations were found between TT20 and CP (0.86, 0.82 and 0.86, all a p < 0.001 for CP1, CP2 and CP3, respectively). The SEE was 17 W, 19 W and 17 W for CP1, CP2 and CP3, respectively. Discussion: In the present study no significant differences in CP were observed when estimated from different trial durations. Irrespective of trial duration, accuracy to predict TT20 was approximately 5%. In accordance with previous studies where TT20 was not significantly different to ventilatory and lactate thresholds, no significant differences were found with CP. This suggests, that TT20 can serve as a surrogate for different thresholds such as ventilatory and lactate thresholds or CP. From a practical point, the use of shorter trial durations does not affect estimates of CP.